Nursery sources and cohort strength of young‐of‐the‐year common carp (Cyprinus carpio) under differing flow regimes in a regulated floodplain river. Issue 2 (20th June 2013) - Macdonald, Jed I.; Crook, David A.
Abstract Otolith chemistry and standardised catch data were used to identify key nursery sources for common carp (Cyprinus carpio) in the mid‐Murray River region, south‐east Australia, and to quantify annual young‐of‐the‐year (YOY) cohort strength under varying hydrological conditions across 4 years (2005/2006–2008/2009). Analysis of trace element concentrations (i.e., Mg:Ca, Mn:Ca, Sr:Ca, Ba:Ca) near the otolith core of post‐larval carp (< 1 month of age) resulted in moderate to very high spatial discrimination of nursery sources within years. Otolith elemental concentrations were not stable across years at all nurseries, necessitating resampling of post‐larvae each spawning season to characterise nursery sources. Annual electrofishing surveys detected a strong cohort of YOY carp (4–6 months of age) in 2006, following a period of natural and artificially augmented high flows in the Murray River main channel and tributaries and extended floodplain inundation in the Barmah‐Millewa Forest (BMF). Few YOY were captured in 2007, 2008 or 2009 – years characterised by low flow conditions in the region and no floodplain inundation in BMF. Maximum likelihood estimation of nursery origins indicated that the BMF was the primary source for YOY fish captured from main channel (Torrumbarry Weir) and tributary (lower Goulburn River) sites in 2006, with the lower Goulburn River making a smaller contribution to the YOY cohort. These results demonstrate the importance of hydrology in determining spatial and temporal patterns of carp recruitment in regulated rivers and highlight the need to consider such factors when attempting to optimise ecological outcomes from environmental flow delivery.